Cysteinyl-leukotriene pathway as a new therapeutic target for the treatment of atherosclerosis related to obstructive sleep apnea syndrome. (August 2018) - Gautier-Veyret, Elodie; Bäck, Magnus; Arnaud, Claire; Belaïdi, Elise; Tamisier, Renaud; Lévy, Patrick; Arnol, Nathalie; Perrin, Marion; Pépin, Jean-Louis; Stanke-Labesque, Françoise
Graphical abstract: Abstract: Aims: Obstructive sleep apnea (OSA) characterized by nocturnal intermittent hypoxia (IH) is associated with atherosclerosis and cysteinyl-leukotrienes (CysLT) pathway activation. We aimed to identify the determinants of CysLT pathway activation and the role of CysLT in OSA-related atherosclerosis. Methods and results: Determinants of the urinary excretion of LTE4 (U-LTE4 ) including history of cardiovascular events, polysomnographic and biological parameters were studied in a cohort of 170 OSA patients and 29 controls, and in a subgroup of OSA patients free of cardiovascular event (n = 136). Mechanisms linking IH, the CysLT pathway and atherogenesis were investigated in Apolipoprotein E deficient (ApoE −/− ) mice exposed to 8-week IH. In the whole cohort, U-LTE4 was independently influenced by age, minimal oxygen saturation, and a history of cardiovascular events, and correlated significantly with intima-media thickness. In the subgroup of OSA patients free of cardiovascular event, increased U-LTE4 was increased compared to controls and independently related to hypoxia severity and traditional risk factors aggregated in the 10-year cardiovascular risk score of European Society of Cardiology. In IH mice, atherosclerosis lesion size and mRNA levels of 5-lipoxygenase, 5-lipoxygenase activating protein (FLAP) and CysLT1 receptor were significantly increased. This transcriptional activation was associated with the binding of HIF-1 to the FLAP promoter and was strongly associated with atherosclerosis lesion size. CysLT1 receptor antagonism (montelukast) significantly reduced atherosclerosis progression in IH mice. Conclusions: IH-related CysLT pathway activation contributes to OSA-induced atherogenesis. In the era of personalized medicine, U-LTE4 may be a useful biomarker to identify OSA patients for whom CysLT1 blockade could represent a new therapeutic avenue for reducing cardiovascular risk.